Student Mobility and Employability: The Ethiopian Experience - Tamrat, Wondwosen; Teferra, Damtew (International Higher Education, 2018)
This article reports the findings of a larger study conducted on international students from Ethiopia to gauge their views on the impact of their training on employability. For those who can afford or have the chance, international studies are perceived as mechanisms of improving one’s employability due to the various advantages they can offer. This has become one of the major pull factors in student mobility.